Innovation Model of Islamic Education Institutions in the Era of Disruption - Hidayatulloh, Muhammad Syarif; Supriyatno, Triyo; Marno, Marno; Maharani, Tiyas Nastiti (EDUTEC : Journal of Education And Technology, 2024)
This study aims to identify innovations in Islamic educational institutions in the era of disruption. The method used in this study is a library research approach, which involves a series of activities related to data collection, reading, recording, and processing research materials from existing literature. The results of this study indicate that in the context of Islamic educational institutions, two key innovations have been implemented to ensure survival in an era of rapid change. Islamic Boarding Schools and Science Pesantren are models of institutional innovation that integrate religious studies and natural sciences.